Perbandingan Pengaruh Metode Latihan Tabata Dengan Metode High Intensity Interval Training Terhadap Hasil Daya Tahan Kardiovaskular Pemain Sepakbola - Nipaldi Hernawan; Andang Rohendi; Gani Kardani (Jurnal Keolahragaan, 2021)
This study aims to determine how much influence the tabata method has on the results of cardiovascular endurance of football players. The research method used is pre experimental design. The population of this research is Chikal FC which is located in Cihaurbeuti, Ciamis Regency, totaling 20 people. The research instrument used to collect data is the bleep test. Based on data analysis using SPSS series 24 the results are 1. The Tabata training method has a significant effect on the cardiovascular endurance results of football players. 2. The HIIT (high intensity interval training) training method has a significant effect on the cardiovascular endurance results of soccer players. 3. There is a significant difference between the Tabata training method and the HIIT (high intensity interval training) training method on the cardiovascular endurance results of soccer players. The conclusion is that the Tabata training method with the HIIT (high intensity interval training) training method has a significant effect on the cardiovascular endurance results of soccer players. Suggestion: This research is expected to be a source of reference for trainers/teachers or other researchers to be used as an alternative method of exercising physical conditions, especially in increasing cardiovascular endurance.Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh metode tabata terhadap hasil daya tahan kardiovaskular pemain sepakbola. Metode penelitian yang digunakan adalah pre expreimental design. Populasi penelitian ini adalah Chikal FC yang berada di Cihaurbeuti Kabupaten Ciamis yang berjumlah sebanyak 20 orang. Instrumen penelitian yang digunakan untuk mengumpulkan data adalah bleep test. Berdasarkan analisis data menggunakan SPSS serie 24 hasilnya adalah 1. Metode latihan Tabata memberikan pengaruh yang signifikan terhadap hasil daya tahan kardiovaskular pemain sepakbola. 2. Metode latihan HIIT (high intensity interval training) memberikan pengaruh yang signifikan terhadap hasil daya tahan kardiovaskular pemain sepakbola. 3. Terdapat perbedaan pengaruh yang signifikan antara metode latihan Tabata dengan metode latihan HIIT (high intensity interval training) terhadap hasil daya tahan kardiovaskular pemain sepakbola. Kesimpulannya bahwa metode latihan Tabata dengan metode latihan HIIT (high intensity interval training) berpengaruh secara signifikan terhadap hasil daya tahan kardiovaskular pemain sepakbola. Saran: Penelitian ini diharapkan menjadi salah satu sumber referensi bagi pelatih/guru atau peneliti lain agar dijadikan alternatif metode latihan kondisi fisik terutama pada peningkatan daya tahan kardiovaskular.